Injustice Behind Rights: Unveiling the Paradox of Wrongful Arrest Victims - Cahya, Sebastian Dwi; Sakmaf, Marius Suprianto; Junaedy, Achmad (Yayasan Sinergi Kawula Muda, 2024)
This research aims to examine the phenomenon of mistaken arrest and its impact on the rights of victims, particularly concerning compensation and rehabilitation mechanisms. Cases of wrongful arrest are frequent in Indonesia; however, the compensation and rehabilitation mechanisms for victims are still suboptimal, resulting in injustice for those whose rights have been violated. This study differs from previous research in that it specifically focuses on the compensation and rehabilitation mechanisms for victims of wrongful arrest in the context of human rights enforcement in the Manokwari region, rather than addressing mistaken arrest cases generally. Qualitative methodology is employed to understand the phenomenon and its implications for human rights in Indonesia. Data is gathered through interviews and document analysis. The study finds that compensation and rehabilitation mechanisms for victims of wrongful arrest still face various normative and non-normative challenges, resulting in injustice for victims who do not fully receive their rights. Legal reforms and increased awareness among law enforcement officials are crucial to ensure the fulfillment of the rights of wrongful arrest victims. The implications of these reforms and increased awareness can lead to a fairer and more accountable criminal justice system, where human rights are respected and protected.